Profesionalitas Guru dalam Penggunaan Ponsel Saat Mengajar: Studi Kasus di SD Negeri 1 Sumampir, Purwokerto Utara - Ruth Geraldine Manurung; Sri Yunita (Departement of Mathematics Education, 2024)
This research examines teacher professionalism in mobile phone usage during teaching at SDN 1 Sumampir. This case study aims to identify patterns of mobile phone use by teachers during the learning process, its impact on teaching quality, and perceptions of students and colleagues. Data collection methods include classroom observations, in-depth interviews, and surveys. The results show variations in mobile phone use by teachers, ranging from educational purposes to personal use. This study also reveals the importance of clear school policies regarding mobile phone use in the classroom to maintain teacher professionalism and learning effectiveness.